The effects of social media marketing activities on brand equity within the South African banking industry: A cohort-based study - Mandhlazi, Lawrence (Vaal University of Technology, 2023)
The South African retail banking industry operates through digital platforms, traditional brick-and-mortar services and automatic teller machines. The online transaction is popularly used because it is easy to use, saves time and money and is also convenient for customers. The most crucial products and services that are promoted on social media include airtime, data bundles, purchasing prepaid electricity, paying for and renewal of vehicle licences, as well as the payment of traffic fines and applying for various instruments such as funerals, study investments, and life policies. The study proposes and tests a conceptual model for social media marketing activities (SMMA), customer brand engagement (CBE) and brand equity (BE) in the retail banking industry in South Africa. Based on the existing review of literature, evidence exists of the inefficient use of social media to actively engage Generation X and Y cohorts, as demonstrated by the high level of complaints and the degree of poor engagement. The study proposes a model that, if tested and then implemented, may prove to be a useful tool for ensuring that the management of SMMA on brand equity is more responsive and useful. This may eventually generate the intended SMMA outcomes in South African retail banks. The study employed a quantitative method in which a purposively selected sample of 352 Generation X and Y individuals based in the Gauteng Province was chosen. Hypotheses were tested using structural equation modelling. The main components of SMMA include perceived risk content, trending content, entertainment content, customisation content, interaction content, value content and electronic-word-of-mouth communication. The results of structural equation modelling (SEM) indicate significant positive interconnections between entertaining content, customisation content and CBE. In turn, CBE exerts a significant positive influence on brand awareness and brand loyalty. The study recommends that financial institutions should integrate customers’ voice towards brand management strategies to ensure that the banking service and brands are more responsive and reflect their holistic preferences within various social media platforms.
D. Com. (Department of Marketing, Faculty of Management Sciences), Vaal University of Technology.
Keywords: Social media marketing; Brand engagement; Brand equity; Banking industry; Dissertations, Academic -- South Africa.; Internet marketing -- Social aspects.; Banks and banking -- South Africa.; Branding (Marketing).